COELIAC DISEASE IN CHILDREN PRESENTING WITH FAILURE TO THRIVE - Ikram, Muhammad Asim; Sajid, Aisha; Hameed, Sadia; Arshad, Kashan; Haq, Irshad -ul- (Journal of Ayub Medical College Abbottabad, 2011)
Background: Coeliac disease used to be considered as a disease of European and Western population but now it has emerged as a global problem. Objective of this study was to evaluate the frequency and mode of presentation of coeliac disease in children presenting with failure to thrive. Methods: This cross-sectional descriptive study was conducted at Paediatrics Department of Madina Teaching Hospital in collaboration with Histopathology Department of University Medical and Dental College, Faisalabad over a period from April 2010 to March 2011. A total of 60 children, aged 4-6 years presenting as failure to thrive according to their height and weight, were included. Relevant investigations were done along with radiological assessment of bone age. The jejunal biopsy was taken in all the patients. Children who were suffering from primary or secondary malnutrition due to other chronic illnesses and malabsorptive syndromes were excluded from the study. The data was analysed using SPSS-17. Chi-square test was used and p<0.05 was considered significant. Results: Total 60 children, 4-16 years of age were included in the study. Twenty-four (40%) children were diagnosed as coeliac disease by jejunal biopsy showing Marsh Grade-3. Male/female ration was 1.5:1. The most frequent symptom among these coeliac patients was abdominal distension (75%, p=0.041), followed by pallor. (71%, p=0.048). Anaemia (Hb<12 gm/dl) was found in all 24 patients. Conclusion: Coeliac disease is increasingly being recognised as presenting with atypical presentation like short stature, failure to thrive, unexplained anaemia, rickets, abdominal distension and abdominal pain. Keywords: Coeliac disease, Failure to thrive, Mixed Deficiency Anaemia